The Effectiveness of Petobo Temporary Shelter - Asiana Rahmawati; Mohammad Mochsen; Abdul Mufti Radja (EPI International Journal of Engineering, 2020)
Temporary shelter (huntara) is one of the government's solutions in undertaking victims after a disaster. Shelter of Petobo is one of the temporary shelters built by the government in the aftermath of the disaster in Palu City in September 28th, 2018. Petobo shelter was built in October and occupied in December. This shelter has a capacity of 70 units. 1 unit of the shelter is measured 26.4m x 12m, it consists of 12 rooms, 4 bathrooms, 4 toilets, a laundry room, and a shared kitchen. The shelter consists of 840 room cubicles with room sizes of 3.6m x 4.8m. After being occupied, some residents said that the shelter they lived in was very small, with family members of more than 3 people, the space for occupants was very limited so that some residents made changes to their residential units. This study evaluates Petobo shelter with BNPB and UNHCR Standards, and examines occupant perceptions about the effectiveness of Petobo shelter in terms of physical building requirements which consist of safety, health, comfort, and convenience. This research was conducted in Palu City, Central Sulawesi. The type of this research is evaluation, using survey methods to measure the value of several variables. The data obtained were analyzed using descriptive statistical techniques. The results of this study indicate that the Petobo shelter is in accordance with BNPB and UNHCR standards, but according to the occupants' perception it is less effective in terms of the physical requirements of the building, which consists of safety, health, comfort, and convenience as a post-disaster refugee residence.